Plurilinguisme et insécurité linguistique en Algérie : Paroles de lycéen (ne)s à Bejaïa - Bachir Bessai (Corela)
This work is based on the hypothesis that there is a relationship between multilingualism and linguistic insecurity. Numerous studies have shown that linguistic insecurity is more frequent in multilingual milieu rather than the unilingual environments. In this range, we have chosen to conduct a survey on some high school students from Bejaïa a city in Algeria. They have been asked to answer some questions that are related to a number of linguistic phenomena occurring in the speech epilinguistics. Throughout this analysis, we have identified various positive and negative attitudes associated with their language. We have therefore tried to list the multiple manifestations of linguistic insecurity, namely, the self-deprecation of their own language, which is undoubtedly one of the major symptoms of linguistic insecurity.